2021
DOI: 10.1007/s12039-020-01872-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of some novel piperidine fused 5-thioxo-1H-1,2,4-triazoles as potential antimicrobial and antitubercular agents

Abstract: A novel series of analogues based on 5-(1-(4-chloro-3-methoxyphenyl)piperidin-4-yl)-4-phenyl-2H-1,2,4-triazole-3(4H)-thione core have been synthesized and their potential as antibacterial, antifungal and antitubercular agents was examined. The structure-activity relationship (SAR) studies of these derivatives 5 (a-k) clearly indicate the vital role of lipophilicity as a major factor in enhancing the biological activity of these compounds. Among the compounds screened, 5a, 5c, 5d, 5j and 5k displayed significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…Azole compounds of the type 1,2,3-triazoles attract more attention as they have excellent biological and physical properties [ 116 , 117 ]. These heterocycles can be obtained by the copper (I) catalyzed 1,3-dipolar cycloaddition reaction of azide and alkyne, as shown in previous reports.…”
Section: Synthetic Methods For Highly Active Compounds Against Fox Speciesmentioning
confidence: 99%
“…Azole compounds of the type 1,2,3-triazoles attract more attention as they have excellent biological and physical properties [ 116 , 117 ]. These heterocycles can be obtained by the copper (I) catalyzed 1,3-dipolar cycloaddition reaction of azide and alkyne, as shown in previous reports.…”
Section: Synthetic Methods For Highly Active Compounds Against Fox Speciesmentioning
confidence: 99%
“…developed piperidine‐fused thiatriazoline hybrids and evaluated them for antitubercular activity. Compound 49 a – b displayed significant anti‐mycobacterial activity against the Mycobacterium tuberculosis H 37 Rv strain [97] . Amongst the piperidine hybrids developed and assessed for anti‐mycobacterial activity by Blanco et al ., compound 50 showed excellent anti‐mycobacterial activity with a MIC<0.02 μM [98] .…”
Section: Anti‐mycobacterial Agentsmentioning
confidence: 99%
“…The electronic properties of nitrogen or sulfur heteroatoms are a significant factor in their selection. One of these compounds, 1,2,4‐triazole, has demonstrated a wide range of biological activities such as antibacterial, [5–7] antimicrobial, [8–10] anti‐HIV, [11–13] antiviral, [14,15] antitumor, [14–16] and antitubercular [17–20] . Researchers have found that modifying the structure of the triazole moiety with specific molecular groups can enhance its biological potency.…”
Section: Introductionmentioning
confidence: 99%
“…One of these compounds, 1,2,4-triazole, has demonstrated a wide range of biological activities such as antibacterial, [5][6][7] antimicrobial, [8][9][10] anti-HIV, [11][12][13] antiviral, [14,15] antitumor, [14][15][16] and antitubercular. [17][18][19][20] Researchers have found that modifying the structure of the triazole moiety with specific molecular groups can enhance its biological potency. Pyrazoles, particularly 1,3,5trisubstituted pyrazoles, have been shown to have significant antitubercular activity with lower MIC values.…”
Section: Introductionmentioning
confidence: 99%